2020
DOI: 10.3390/s20143857
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vertical Ground Reaction Forces Pattern Visualization in Neurodegenerative Diseases Identification Using Deep Learning and Recurrence Plot Image Feature Extraction

Abstract: To diagnose neurodegenerative diseases (NDDs), physicians have been clinically evaluating symptoms. However, these symptoms are not very dependable—particularly in the early stages of the diseases. This study has therefore proposed a novel classification algorithm that uses a deep learning approach to classify NDDs based on the recurrence plot of gait vertical ground reaction force (vGRF) data. The irregular gait patterns of NDDs exhibited by vGRF data can indicate different variations of force pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
0
28
1
Order By: Relevance
“…For the classification of the HC group and each disease from NDD groups, the proposed algorithm outperforms or equal to the performance to that of the [ 11 , 12 , 13 , 14 , 15 , 16 ]. For classification of any two disease groups from NDD groups, the performance of this study outperforms that of the [ 11 , 12 , 13 , 16 ] but little less than [ 14 ]. However, the accuracy is less than 0.5%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For the classification of the HC group and each disease from NDD groups, the proposed algorithm outperforms or equal to the performance to that of the [ 11 , 12 , 13 , 14 , 15 , 16 ]. For classification of any two disease groups from NDD groups, the performance of this study outperforms that of the [ 11 , 12 , 13 , 16 ] but little less than [ 14 ]. However, the accuracy is less than 0.5%.…”
Section: Discussionmentioning
confidence: 99%
“…The main contribution of this study can be found by comparing the existing literature using the same database [ 9 ]. Table 9 reveals the classification results of the proposed algorithm comparing to other literature [ 11 , 12 , 13 , 14 , 15 , 16 ], the time window length of 10-sec with the KNN model from the proposed algorithm are used to compare with other literature. For the classification of the HC group and each disease from NDD groups, the proposed algorithm outperforms or equal to the performance to that of the [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations